GPS2 (GREEN PIPE SYSTEM STATE): REKAYASA SIKLUS AIR DENGAN SISTEM SALURAN AIR NEGERI PIPA UNTUK MENANGGULANGI BANJIR DI JAKARTA - Hasanah, Nur; Perdana, Hafidh Frian; Ghofur, Abdul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Floods hit Jakarta every year. The three-meter high floods, due to overflowing Ciliwung River, hit Kampung Pulo, Kampung Melayu, Jatinegara, East Jakarta (Wednesday, 13/02/2013). This paper aims to formulate the concept of watershed improvements in Jakarta. The concept promotes environmental innovation systems in the watershed named GPS2 (Green Pipe System State). GPS2 is a series of elements that are connected to one another. GPS2 important element is the principle of circular motion, the principle of water flow, the concept of using a pipe drains, the concept of river water filters that are free of trash, removal of the concept of river water to flow smoothly, the concept of green areas in the watershed, and the concept of with a maximum water absorption by trees and holes in the catchment basin and certain areas are frequently flooded.GPS2 system workflow begins with the screening of garbage on the main river by using circular motion. Garbage is lifted to the river bank whilst filtered water enters into the main channel then undergoes filtration on filter 1 to produce water clean. The water is removed and undergone a screening process again on the filter 2 and the resulting clean water is ready to circulate to the area around GPS2. The water flowed through the pipes supported by trees that also serves to increase the amount of green open space in the city. The water will be stored in the water tank or directly utilized by residents. In addition to filtered water flows, a small stream flowed even more clear to maintain the balance of the ecosystem. GPS2 has enormous benefits such as overcoming the problem of flooding in the capital of Jakarta, helping provide clean water, adding a green open space as well as addressing issues, in particular garbage in the river.